ANALISIS KEBUTUHAN GURU TERHADAP BAHAN AJAR DIGITAL IPA BERBASIS LEARNING CYCLE 5E DI SEKOLAH DASAR - Anjani, Parra; Usman, Herlina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to develop a digital Science instructional material based on the 5E learning cycle to enhance elementary school students' learning outcomes. The research method employed Research & Development with the ADDIE approach, consisting of Analysis of Needs, Design of instructional material, Development of instructional material, Implementation, and Evaluation stages. Data collection was conducted through interviews and questionnaires to gather information from the analysis of the needs of 20 elementary school students and 3 class teachers. The analysis results indicate that 66.7% of teachers state the necessity of digital instructional material to improve students' learning outcomes. Meanwhile, interviews with students reveal the need for easily accessible, interactive, and engaging instructional materials. Both students and teachers responded positively to the development of digital instructional materials in Science learning. In conclusion, the analysis underscores the crucial need for digital Science instructional material based on the 5E learning cycle as additional teaching resources. keywords: digital material;science; 5E learning cycle; elementary school